Moralne dylematy rozwoju społeczeństw ponowoczesnych - Płachciak, Adam (Annales. Etyka w Życiu Gospodarczym, 2008)
The aim of the article is to present tensions that occur in social, cultural, political,and technological spheres as the result of the development of postmodern societies. The changes thathave been taking place in those areas involve, along with unquestionable benefits, a type of risk which,without any moral reflection, can cause a serious global crisis in the world. The postmodern timesshould be understood as the continuation of the modern formation where all typical featuresof modernism take a more radical form. The postmodern specific style of life is characterized by:uncertainty, unpredictability of future, decline of traditional values and morals. What is more,the present postmodern tendencies in the area of morals can hinder the right course of developmentfor society, economy and ecology.